Evaluation of visit‐to‐visit blood pressure variability on global cognitive impairment and cognitive decline in an ethnically diverse cohort: The multi‐ethnic study of atherosclerosis. (31st December 2021) - Daniel, George; Hughes, Tim M; Bertoni, Alain; Chen, Haiying; Hayden, Kathleen M
Abstract: Background: Hypertension and diabetes are key modifiable risk factors for Alzheimer's disease and related dementias. Research has typically focused on blood pressure (BP) levels, despite evidence that high BP variability (BPV) over time may predict poorer cardiovascular, neuropathological, and neurocognitive outcomes. We assessed associations between BPV and global cognition in a cohort of participants from the Multi‐Ethnic Study of Atherosclerosis (MESA), including 4 ethnoracial groups: White, African‐American, Chinese, and Hispanic. Methods: Longitudinal BP data across 6 MESA examinations were used in multivariable linear and logistic regression analyses to determine the association BPV and cognitive function, decline, and incident impairment. Two measures of long‐term BPV (Average Real Variability [ARV] and Variability Independent of the Mean [VIM]) and group‐based latent BP trajectories were estimated over an average of 9.4 years. The Cognitive Abilities Screening Instrument (CASI), Digit Symbol Coding (DSC), and Digit Span (DS), were administered at MESA Exams 5 and 6, an average of 6.3 years apart. This enabled the assessment of cognitive function, decline, and cognitive impairment, defined as performance in the lowest 10% of groups stratified by age, education, and race. Results: Participants (N=1314) had a mean baseline age of 57 years, and were 50% female and 48% White. Increased systolic and diastolic BPV were associated with poorer performance across all measures and with increased global cognitive decline in unadjusted models. Higher systolic (β = ‐0.06, P =0.05) and diastolic (β = ‐0.08, P =0.005) ARV was predictive of increased CASI decline after adjustment for demographic and clinical characteristics, including mean BP. Significant interactions and subsequent stratified analyses indicated that the strongest relationships between BPV and global cognition were in participants older than age 65, White or Black, APOE ε4 non‐carriers, males, and non‐antihypertensive medication users. Higher and more variable latent systolic and diastolic BP trajectories predicted reduced performance on the CASI, DS, or DSC tests before and after adjustment for clinical and demographic characteristics. Conclusion: Results suggest high BPV is a risk factor for global cognitive dysfunction and decline, independent of mean BP levels, in this middle‐aged, healthy, and multi‐ethnic population. Relationships may differ across demographic, genetic, and clinical characteristics.